A Novel Capacitor Voltage Balancing Method for MMCs with Less Computation and Lower Switching Frequency. (August 2019) - Gou, Xin; Lu, Jiping; Deng, Wenling
Abstract: Aiming at the computation complexity and high switching frequency existing in conventional voltage balancing method of high-level modular multilevel converters (MMCs), a novel capacitor voltage balancing method based on insertion priorities of sub-modules (SMs) is proposed. Instead of sorting the voltage values of SMs, an Allowable Capacitor Voltage Distribution Band (ACVDB) is applied to constrain the fluctuation range of capacitor voltages. And the insertion priorities of SMs in current control cycle are determined by comparing their voltage values in last control cycle with the upper and lower limits of ACVDB respectively. The effectiveness of the proposed method is validated by a 41-level MMC model in MATLAB/Simulink R2017a. Simulation results demonstrate that the switching frequency can be reduced significantly with an allowable deviation of capacitor voltages in both steady state and transient process.